Theoretical and experimental study of the factors of sterilization of medical articles in low pressure glow discharge plasma - Soloshenko, I.A.; Tsiolko, V.V.; Khomich, V.A.; Schedrin, A.I.; Ryabtsev, A.V.; Bazhenov, V.Yu.; Mikhno, I.L. (Вопросы атомной науки и техники, 2000)
In the report the results of experimental and theoretical studies of the parameters of direct current glow discharge plasma are presented. The efficiencies of its main sterilizing factors (charged particles, electrically neutral chemically active particles and ultraviolet radiation of the plasma) are also studied. The prospects of the use of such discharge for cold sterilization of medical instruments is estimated.